Cover crops lower soil surface strength, may improve soil permeability - O Folorunso; D Rolston; P Prichard; D Louie (California Agriculture, 1992)
Poor water penetration constitutes a major production constraint for more than 400, 000 acres of agricultural land in California. The associated economic losses are particularly appreciable in the production of fruit and nut crops. In response to a hypothesis that cover crops may improve water infiltration in orchards, studies were conducted at Davis and Ceres. After 3 years' study, results indicate major benefits are possible with the planting of cover crops.